Potential Prognostic Role for SPOP, DAXX, RARRES1, and LAMP2 as an Autophagy Related Genes in Prostate Cancer - Jamali, Leila; Moradi, Afshin; Ganji, Maziar; Ayati, Mohsen; Kazeminezhad, Behrang; Fazeli Attar, Zahra; Ghaedi, Hamid; Ghaderian, Seyyed Mohammad Hossein; Fallah-Karkan, Morteza; Ranjbar, Arash (Urology Journal, 2020)
Purpose: Autophagy plays a critical role in PCa development. DAXX has a potent pro-survival effect by enhancing cell growth in PCa via suppression of autophagy. Here, we depicted a network governed by DAXX and SPOP by which the autophagy pathway is suppressed through the ubiquitination and modulation of key cellular signaling pathways mediators including LAMP2 and RARRES1. Materials and Methods: Through network-based bioinformatics approaches, the expression levels of DAXX, RARRES1, LAMP2, and SPOP genes was assessed in 50 PCa tissues and 50 normal adjacent from the same sample as well as 50 benign prostatic hyperplasia (BPH) tissues by quantitative RT-PCR. The normal adjacent tissues were taken from regions more than 5mm away from the bulk of those tumor tissues with clearly distinct margins. RNA extraction, cDNA synthesis and Real-time Quantitative RT-PCR were done for assessment of gene expression. To evaluate the primary gene network centered on autophagy pathway, according to the Query-dependent weighting algorithm, these two networks were integrated with Cytoscape 3.4 software. Results: We found that in PCa tissues the DAXX expression level was significantly increased (P < 0.001) and the expressions of SPOP, RARRES1, and LAMP2 were significantly down-regulated, when compared to both control groups including normal adjacent and BPH tissues. Moreover, significant correlations were observed between expression levels of all four genes. Additionally, ROC curve analysis revealed that LAMP2 had the most sensitivity and specificity. Conclusion: These findings suggest that the contribution of SPOP, DAXX, RARRES1, and LAMP2 together could be a putative regulatory element acting as a prognostic signature and therapeutic target in PCa.